1985
DOI: 10.1210/jcem-61-6-1031
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies to Human Chorionic Gonadotropin: Implications for Antigenic Mapping, Immunoradiometric Assays, and Clinical Applications**

Abstract: Monoclonal antibodies to intact hCG and free beta-subunit of hCG permit the recognition of different individual antigenic sites on the hCG molecule. At least seven different epitopes may be recognized on the native molecule and a further two on the free beta-subunit. These antibodies were used in a mouse Leydig cell bioassay system to compare the degree of inhibition of hCG-induced testosterone production. Two antibodies were particularly potent at inhibiting hCG action, suggesting that they bind near to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

1987
1987
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 27 publications
1
26
1
Order By: Relevance
“…Until recently, RIAs were the method of choice for the measurement of hCG [14], The advent of monoclonal antibodies enabled immunoradiometric assay procedures (IRMA) to improve on RIA methods in terms of speed, sensitivity and specificity [1,10], A technical advantage of IRMA procedures over RIA is that they can be designed to respond specifically to dimer hCG with minimal cross-reactiv-ity with free P-hCG subunit. This may be a clinical disadvantage, however, if significant amounts of free P-hCG subunit accompany hCG secretion in malig nancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, RIAs were the method of choice for the measurement of hCG [14], The advent of monoclonal antibodies enabled immunoradiometric assay procedures (IRMA) to improve on RIA methods in terms of speed, sensitivity and specificity [1,10], A technical advantage of IRMA procedures over RIA is that they can be designed to respond specifically to dimer hCG with minimal cross-reactiv-ity with free P-hCG subunit. This may be a clinical disadvantage, however, if significant amounts of free P-hCG subunit accompany hCG secretion in malig nancy.…”
Section: Discussionmentioning
confidence: 99%
“…The development of mono clonal antibodies, however, enables immunoassays to respond to the presence of intact or dimer hCG with minimal cross-reaction with its free a-or P-subunit [11]. In monitoring malignancy using hCG levels, re cent reports [6,10] have suggested that highly specific dimer hCG immunoassay may have less prognostic value than assays that respond to the free subunits as well as the dimer hCG. In the present study, mono clonal antibodies specific to free tt-and free P-hCG subunits were used to establish homologous assays.…”
Section: Introductionmentioning
confidence: 99%
“…The use of two or more monoclonal antibodies in combination can assist in the construction of assays or predefined specificity such as free IX or P subunits, Pcore, intact hCG, etc. 23 • 30…”
Section: )mentioning
confidence: 99%
“…The free p subunit concentration peaks early in the pregnancy and falls rapidly while the free IX subunit concentration rises progressively throughout gestation. 23 • 33…”
Section: )mentioning
confidence: 99%
“…It is noteworthy that levels up to 5 IU/1 occur normally in menopausal women; in women of fertile age, the levels do not exceed 2 IU/1 [5]. Assays that measure directly the free P-subunit of HCG are becoming avail able [5,6], It remains to be seen whether such assays will be useful for the clinical management of choriocarcinoma patients.…”
Section: Trophoblastic Diseasementioning
confidence: 99%